2014
DOI: 10.1080/10413200.2014.996302
|View full text |Cite
|
Sign up to set email alerts
|

Effective Ways to Develop and Maintain Robust Sport-Confidence: Strategies Advocated by Sport Psychology Consultants

Abstract: 26Based on recent evidence (Thomas, Lane, & Kingston, 2011), this study identified 10 27 strategies advocated by sport psychology consultants as effective at developing and by sport psychology consultants. 52Self-confidence is frequently cited as an important part of successful sport 53 performance and has been shown to influence behaviors, attitudes, and sporting attainment 54 (Cox, Shannon, McGuire, & McBride, 2010). The two theoretical frameworks that have 55 predominantly been used to study self-confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 29 publications
6
59
1
1
Order By: Relevance
“…In sport psychology, it has been suggested that our discipline has exemplified positive psychology for the last 25 years, through the study of athletic excellence (Gould, 2002). While it is recognized that this focus on excellence is apparent in some sport psychology research, specific strengths-based consultancy approaches/methods, and the potential benefits of adopting these have only -63 -recently been alluded to (i.e., Beaumont, Maynard, & Butt, 2015;Gordon & Gucciardi, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In sport psychology, it has been suggested that our discipline has exemplified positive psychology for the last 25 years, through the study of athletic excellence (Gould, 2002). While it is recognized that this focus on excellence is apparent in some sport psychology research, specific strengths-based consultancy approaches/methods, and the potential benefits of adopting these have only -63 -recently been alluded to (i.e., Beaumont, Maynard, & Butt, 2015;Gordon & Gucciardi, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of the factors identified to be positively influenced via strengths-based approaches are relevant and desirable in a sporting context, including goal progress/attainment (Fluckiger & Grosse Holtforth, 2008;, psychological needs satisfaction , well-being (Govindji & Linley, 2007;, engagement and performance (CLC, 2002;Clifton & Harter, 2003). In sport psychology, it has been suggested that strengths-based approaches could potentially be used to aid development of athletes' mental toughness (Gordon & Gucciardi, 2011), robust sport confidence (Beaumont et al, 2015), and other psychological factors associated with optimal performance (Wagstaff & Leach, 2015). However, studies actually employing strengths-based interventions to assess the role or impact of this way of -36 -working are scarce, highlighting a significant gap in our knowledge and understanding of this area.…”
Section: Summary and Aims Of The Thesismentioning
confidence: 99%
See 3 more Smart Citations